Tingkat Kepuasan Pasien Terhadap Pelayanan Perawat Di Klinik Sembuh Lukaku Universitas Muhammadiyah Magelang - Reczy Kurnia Vendy; Sodiq Kamal; Rohmayanti Rohmayanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The abstract must be short, interesting, simple, and easy to understand without reading the entire article. Therefore, avoid jargon, abbreviations and references. In writing abstracts, the author must be accurate, use the right words, and convey the meaning of the study. A good abstract contains the problem statement and purpose, how the research is carried out (the method), the results, and concludes with a brief statement of conclusions. In the abstract keywords are also always included. Keywords are used to index an article and are the label of an article. Background: The level of satisfaction is a reflection of the quality of service. Patient satisfaction is the result of an assessment in the form of an emotional response to feelings of pleasure and satisfaction in patients because of the fulfillment of expectations or desires in using and receiving nurse services. Objective: This study aims to determine the level of patient satisfaction with the services of nurses at the Lukaku recovery clinic, Muhamadiyah University, Magelang. This study uses primary data sourced from direct observation and questionnaires distributed to respondents . Methods: This study used a questionnaire which was filled out by the respondents. Sampling used accidental sampling, namely the researcher took respondents at that time at the Lukaku Healing Clinic as many as 29 respondents. Results: The results of the data analysis revealed that the variables reliable, assurance, tangible, empathy, responsiveness affect the level of patient satisfaction with the services of nurses at the Healing Clinic. Lukaku